Biodegradation of Ether Pollutants by Pseudonocardia sp. Strain ENV478 - Vainberg, Simon (American Society for Microbiology, 2006)
A bacterium designated Pseudonocardia sp. strain ENV478 was isolated by enrichment culturing on tetrahydrofuran (THF) and was screened to determine its ability to degrade a range of ether pollutants. After growth on THF, strain ENV478 degraded THF (63 mg/h/g total suspended solids [TSS]), 1,4-dioxane (21 mg/h/g TSS), 1,3-dioxolane (19 mg/h/g TSS), bis-2-chloroethylether (BCEE) (12 mg/h/g TSS), and methyl tert-butyl ether (MTBE) (9.1 mg/h/g TSS). Although the highest rates of 1,4-dioxane degradation occurred after growth on THF, strain ENV478 also degraded 1,4-dioxane after growth on sucrose, lactate, yeast extract, 2-propanol, and propane, indicating that there was some level of constitutive degradative activity. The BCEE degradation rates were about threefold higher after growth on propane (32 mg/h/g TSS) than after growth on THF, and MTBE degradation resulted in accumulation of tert-butyl alcohol. Degradation of 1,4-dioxane resulted in accumulation of 2-hydroxyethoxyacetic acid (2HEAA). Despite its inability to grow on 1,4-dioxane, strain ENV478 degraded this compound for >80 days in aquifer microcosms. Our results suggest that the inability of strain ENV478 and possibly other THF-degrading bacteria to grow on 1,4-dioxane is related to their inability to efficiently metabolize the 1,4-dioxane degradation product 2HEAA but that strain ENV478 may nonetheless be useful as a biocatalyst for remediating 1,4-dioxane-contaminated aquifers.